Zerstörung von Geschriebenem Historische und transkulturelle Perspektiven - Kühne-Wespi, Carina; Oschema, Klaus Peter; Quack, Joachim Friedrich (Materiale Textkulturen, 2019)
Inscribed artifacts are exposed to a range of practices that damage them. These practices vary dramatically across historical periods and cultural contexts. This book studies a number of representative examples spanning ancient, medieval, and modern times. The analysis identifies features of these different practices and the motivations behind them, developing a comprehensive system of interpretation.